2018
DOI: 10.15666/aeer/1604_51575174
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Assessment of Tekala River, Selangor, Malaysia

Abstract: A study on water quality status of Tekala River, Selangor, Malaysia was conducted at two sampling times. A total of six sampling stations were selected along the river representing the upstream (S1 and S2), the middle stream (S3 and S4) and the downstream (S5 and S6) of the Tekala River. In this study, in-situ and ex-situ analyses were conducted to determine the quality of Tekala River. Physical, chemical and biological parameters included biochemical oxygen demand (BOD), chemical oxygen demand (SOD), ammoniac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…Both results had shown that the tests were above WHO standards before the treatment plants. The fecal coliform & E.coli tests after water treatment plant was with the range of acceptable standards.Similar studies on E. coli & total coliform were 1-16 CFU/ml & 3-48 CFU/ml in Malaysian river water respectively(24), which were lower than Asella municipality water supply findings.The ammonia concentration throughout the study sites was above WHO recommends to occur until 0.2mg/L (3) for surface water from site 2 to site 5. The finding of ammonia availability was an indication of water pollution by bacteria, sewage & animal waste.…”
supporting
confidence: 66%
“…Both results had shown that the tests were above WHO standards before the treatment plants. The fecal coliform & E.coli tests after water treatment plant was with the range of acceptable standards.Similar studies on E. coli & total coliform were 1-16 CFU/ml & 3-48 CFU/ml in Malaysian river water respectively(24), which were lower than Asella municipality water supply findings.The ammonia concentration throughout the study sites was above WHO recommends to occur until 0.2mg/L (3) for surface water from site 2 to site 5. The finding of ammonia availability was an indication of water pollution by bacteria, sewage & animal waste.…”
supporting
confidence: 66%
“…TSS are solid in a water body which includes a wide variety of materials, such as silt, decaying plants, animal matters, and other solid wastes [26]. Figure 2 shows the reduction rate of TSS using 50 g of C. asiatica, I. aquatica, S. molesta, P. stratiotes, and E. crassipes plotted against the days of treatment.…”
Section: Reduction Rate Of Tssmentioning
confidence: 99%
“…The variation in the WQI value is affected by anthropogenic factors. Example River areas and areas around agricultural land around cities get more polluted than those that are not [38,39]. Spatial destruction proves a parallel result as Class III of WQI with a few variations to the river plan change in water quality is higher compare others.…”
Section: Spatial Modelmentioning
confidence: 96%